Disharmonization Of Regional Regulation Of Samarinda Number 2 Of 2019 On State Land Clearing Permit: Disharmonisasi Peraturan Daerah Kota Samarinda Nomor 2 Tahun 2019 Tentang Izin Membuka Tanah Negara - helmi, Muhammad Helmi (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2025)
In the land sector, this is a central government authority that is delegated to the regions. Does the local government have complete or partial authority?. This research is normative with a legislative and comparative approach. The results of the study are disharmonization in the IMTN Regional Regulation of Samarinda City, where the phrase "remembering" only refers to 4 legal bases, while the IMTN Regional Regulation of Bangka Regency lists 18 legal bases. Second, Refeal of the IMTN City Regulation Article 6 paragraph 9 is contrary to the Republic of Indonesia Government Regulation Number 16 of 2004 concerning Land Use in the explanation of Article 6 Letter b. Third, Article 6 paragraph 9 is contrary to Article 1 number 10 and number 11, even though the provisions are in one regulation. Fourth, there was disharmony in several sub-districts in determining IMTN applicants. Fifth, Article 11 paragraph (3) of the IMTN City Regulation contradicts Government Regulation Number 24 of 1997 concerning Land Registration Article 24 paragraph (2) and Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units and Land Registration Article 97. The recommendations in this study are: first, to revise (add) the source of legal retrieval, the provision is a higher regulation on the phrase "remembering". Second, IMTN is land that is directly controlled by the state, and it has not been registered. Third, refeal of Article 6 paragraph 9. Fourth, The Mayor of Samarinda determines who the IMTN applicant and also the Statement of Physical Control of the Land Area. Fifth, refeal of Article 11 paragraph 3. Sixth, to socialize the community about changing the name of IMTN rights and previous legal basis by submitting a certificate registration as per the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Provisions for the Implementation of Government Regulation Number 24 of 1997 concerning Land Registration Article 60 paragraph (2) Letter h. Fourth, refeal of Article 11 paragraph 3. Seventh, after the socialization during the revision of the Samarinda City IMTN Regional Regulation, it must undergo an academic study.